Degradation of interleukin 1beta by matrix metalloproteinases. - Ito, A; Mukaiyama, A; Itoh, Y; Nagase, H; Thogersen, I; Enghild, J; Sasaguri, Y; Mori, Y (1996)
Matrix metalloproteinases (MMPs) and interleukin 1 (IL-1) are implicated in inflammation and tissue destruction, where IL-1 is a potent stimulator of connective tissue cells to produce the extracellular matrix-degrading MMPs. Here, we report that IL-1beta, but not IL-1alpha, is degraded by MMP-1 (interstitial collagenase), MMP-2 (gelatinase A), MMP-3 (stromelysin 1), and MMP-9 (gelatinase B). This degradation was effectively blocked by tissue inhibitor of metalloproteinases (TIMP)-1. When IL-1beta was treated with MMPs it lost the ability to enhance the synthesis of prostaglandin E2 and pro-MMP-3 in human fibroblasts. The primary cleavage site of IL-1beta by MMP-2 was identified at the Glu25-Leu26 bond. These results suggest that IL-1beta stimulates connective tissue cells to produce MMPs, but activated MMPs in turn negatively regulate the activity of IL-1beta.